Perception and sustainable plastics. A digital tool to manage aesthetics and sustainability - Barbara Del Curto; Lia Sossini; Romina Santi; Flavia Papile (Agathón, 2022)
Today, designers find expression through project design but also assume an active role in the application of new materials, becoming both researchers and experts in the management of aesthetics and sensoriality. Sustainable plastics are relatively new on the market, but, despite considerable application interest, they do not yet have a clear aesthetic-sensory identity. This study explores the aesthetic-expressive properties of sustainable plastics according to the principles of CMF design and aims to investigate user perception. The data, collected through two surveys, has enabled the development of a digital tool to create greater awareness in designers wishing to approach design with sustainable plastics and enhance their perceptual effects.